Innovating Islamic Education Through Technology: Strategies for Overcoming Challenges in Online Learning - Rulitawati, Rulitawati; Sriyanti, Sriyanti; Zainuddin, Muhammad; Hadi, Azwar; Asvio, Nova (Graduate Program Magister Manajemen Pendidikan, 2025)
This study explores the implementation of online learning in Islamic Education (PAI) using the Independent Curriculum and offers solutions to overcome these obstacles. Using a qualitative methodology, data were collected through in-depth interviews and literature reviews from various sources, including books, scientific publications, and interviews with PAI teachers at SMA Muhammadiyah 1. The key findings reveal three main challenges: a lack of parental involvement, low digital literacy among teachers and students, and unequal access to technology. Furthermore, the limited availability of engaging, contextual, and digital-based PAI content poses significant difficulties. This study recommends enhancing teacher training in digital literacy, developing technology-based PAI learning resources, and fostering collaboration with communities, parents, and schools. To increase student interest, it emphasizes project-based learning methods and the integration of Islamic technologies, such as digital Quran applications. This research aims to support the development of relevant and effective PAI learning strategies for the digital era.